Transactional analysis counselling: an introduction - Sami, Mahbuba Naznin; Karim, Shamim F. (BRAC University, 2010)
Transactional analysis is a systematic tool for personal growth and development. In Transactional Analysis counselor does counseling for developing adult ego states of the client. Though all time an individual behaves, thinks and feels from different ego states like as parent, adult or child ego states. Besides these, we can structure our time with the help of different techniques such as withdrawal, activity, rituals, past time, games, rackets and intimacy. There is a contract between client and counselor in the counseling session. By using Transactional Analysis and proper contract client can achieve his goal easily and maintain a peaceful life by improving his adult ego state.